Exploring the accuracy of school-based English test items for grade XI students of senior high schools - Martin Iryayo; Agus Widyantoro (REID (Research and Evaluation in Education), 2018)
This study is set out to (1) explore the accuracy of school-based English test items developed by English teachers and (2) compare the relationship between the content covered by teacher and the students’ success level. This research used the quantitative approach. The source of the data is all grade XI students’ answers to the English test for the second semester of 2016/2017 academic year, and their English teachers’ responses to the questionnaire. During this cross-sectional survey, 241 grade XI students and six English teachers were selected by using the total population sampling technique. To analyze the data, the IRT model was prioritized with BILOG MG 3.0, WINISTEPS 3.7. The findings of the study indicate that (1) the test is valid, (2) it is reliable, (3) majority of the items are moderately difficult, (4) more than a half of all items have power to discriminate the examinees, (5) some items show fully-effective distractors, and (6) the test gives much information at -.40 of theta which means that the test is difficult for the grade XI students. Moreover, there is a wide gap between the content covered and the level of success.